Studi Fenomenologi Makna Dukungan Keluarga terhadap Kejadian Depresi pada Lansia di Kabupaten Wajo - Ikdafila Ikdafila; Arni AR; Barangkau Barangkau; Fitri Apriani (Journal Research of Nursing & Midwifery (JRNM), 2025)
Elderly individuals are a vulnerable group prone to mental health disorders, especially depression. Family support serves as a protective factor that can influence the psychological well-being of the elderly, yet its impact is often underexplored. This study aims to explore the meaning of family support in relation to depression among elderly individuals, particularly within the context of their daily lives. The study uses a qualitative approach with a phenomenological design. Ten elderly informants experiencing mild to moderate depressive symptoms were selected through purposive sampling and interviewed in-depth. The data were analyzed using Colaizzi's analysis method, which consists of seven stages: reading the transcripts, extracting significant statements, formulating meanings, grouping meanings into themes, creating a comprehensive description, describing the essence structure of the phenomenon, and validating with the participants. From the data analysis, four main themes emerged reflecting the elderly's experiences related to family support: (1) Emotional support as a mental strength for the elderly, (2) Family involvement in daily activities as a form of attention, (3) Barriers in intergenerational communication within the family, and (4) Feelings of loneliness due to lack of family interaction. Family support plays a crucial role in helping the elderly cope with depression. The physical presence of family, empathetic communication, and active involvement in daily activities can provide a sense of security and being valued for the elderly. This study emphasizes the importance of family-based interventions for the prevention and management of depression in the elderly.